Subcellular Localization Screening of Colletotrichum higginsianum Effector Candidates Identifies Fungal Proteins Targeted to Plant Peroxisomes, Golgi Bodies, and Microtubules - Robin, Guillaume P.; Kleemann, Jochen; Neumann, Ulla; Cabre, Lisa; Dallery, Jean-Félix; Lapalu, Nicolas; O’Connell, Richard J. (Frontiers in Plant Science, 2018)
The genome of the hemibiotrophic anthracnose fungus, Colletotrichum higginsianum, encodes a large inventory of putative secreted effector proteins that are sequentially expressed at different stages of plant infection, namely appressorium-mediated penetration, biotrophy and necrotrophy. However, the destinations to which these proteins are addressed inside plant cells are unknown. In the present study, we selected 61 putative effector genes that are highly induced in appressoria and/or biotrophic hyphae. We then used Agrobacterium-mediated transformation to transiently express them as N-terminal fusions with fluorescent proteins in cells of Nicotiana benthamiana for imaging by confocal microscopy. Plant compartments labelled by the fusion proteins in N. benthamiana were validated by co-localization with specific organelle markers, by transient expression of the proteins in the true host plant, Arabidopsis thaliana, and by transmission electron microscopy-immunogold labelling. Among those proteins for which specific subcellular localizations could be verified, nine were imported into plant nuclei, three were imported into the matrix of peroxisomes, three decorated cortical microtubule arrays and one labelled Golgi stacks. Two peroxisome-targeted proteins harbored canonical C-terminal tripeptide signals for peroxisome import via the PTS1 (peroxisomal targeting signal 1) pathway, and we showed that these signals are essential for their peroxisome localization. Our findings provide valuable information about which host processes are potentially manipulated by this pathogen, and also reveal plant peroxisomes, microtubules and Golgi as novel targets for fungal effectors.